The Responses of Light Reaction of Photosynthesis to Dynamic Sunflecks in a Typically Shade-Tolerant Species Panax notoginseng - Zhang, Jin-Yan; Zhang, Qiang-Hao; Shuang, Sheng-Pu; Cun, Zhu; Wu, Hong-Min; Chen, Jun-Wen (Frontiers in Plant Science, 2021)
Light is highly heterogeneous in natural condition, and plants have to evolve strategies to acclimate the dynamic light. The present study aimed to elucidate the response of light reaction with respect to dynamic sunflecks, and to examine the regulatory mechanisms involved in an adaptation to a simulated sunfleck. Panax notoginseng was exposed to simulated sunflecks, NPQ increased to the maximum. Moreover, in response to simulated sunflecks, there was also an increase in ΦNPQ, while the Fv'/Fm' declined. High fluorescence and constitutive heat dissipation quantum efficiency of PSII (Φf, d) in plants exposed to transient high light was accompanied by low effective photochemical quantum yield of PSII (ΦPSII) after dark recovery, whereas plants exposed to transient low light lead to elevation in ΦPSII after darkness recovery. Furthermore, PSII fluorescence and constitutive heat dissipation electron transfer rate (Jf,d) was increased with intensity of simulated sunflecks, the residual absorbed energy used for non-net carboxylative processes (JNC) was decreased when the response of electron transfer rate of non-photochemical quenching pathway of PSII (JNPQ) to transient low light is restricted. In addition, the acceptor-side limitation of PSI (Y(NA)) was increased, while the donor-side limitation of PSI (Y(ND)) was decreased at transient high light accompanied with active cyclic electron flow (CEF). Meanwhile, exposure to transient high light, the xanthophyll cycle was actived and subsequently the JNPQ was increased. The de-epoxidation state was correlated with NPQ in response to a sunfleck. A rapid engagement of lutein epoxide (Lx) after low intensity of sunfleck together with the lower NPQ contributed to an elevation in the maximum photochemical quantum efficiency of PSII in the light. The correlation between CEF and electron flow devoted to RuBP oxygenation (JO) indicated that at high light intensity of sunflecks, the electron flow largely devoted to RuBP oxygenation would contribute to the operation of the cyclic electron flow. Overall, photorespiration plays an important role in regulating the cyclic electron flow in response to transient high light, whereas active Lx cycle together with decelerated non-photochemical quenching may be an effective mechanism of elevating the maximum photochemical quantum efficiency exposure to transient low light.